2021
DOI: 10.1007/s10584-021-02998-1
|View full text |Cite
|
Sign up to set email alerts
|

Compensation effect of winter snow on larch growth in Northeast China

Abstract: Winter snow plays a crucial role in regulating tree growth during the subsequent growing season in regions suffering seasonal or even annual drought stress, but the mechanisms of the potential compensation effect of winter snow on subsequent growing-season tree growth are not well understood. In this study, we establish tree-ring chronologies of six larch forest stands along a marked drought gradient across Northeast China. We identify the spatial pattern in the compensation effects of winter snow on subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Wu et al [27] suggested that snow is an important driver of tree growth in regions where growing-season precipitation is limited. Li et al [34] also found that winter snow plays a crucial role in regulating tree growth during the subsequent growing season in regions that experience seasonal or even annual drought stress. These studies and our results show that winter snow has an important impact on the radial growth of trees in precipitation-limited regions.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al [27] suggested that snow is an important driver of tree growth in regions where growing-season precipitation is limited. Li et al [34] also found that winter snow plays a crucial role in regulating tree growth during the subsequent growing season in regions that experience seasonal or even annual drought stress. These studies and our results show that winter snow has an important impact on the radial growth of trees in precipitation-limited regions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also suggest that the climatic response of trees varies regionally, possibly reflecting different climatic limitations on tree growth across study areas [55]. Areas with less summer precipitation rely on winter precipitation for replenishment [57], while the negative response to winter precipitation in regions with abundant rainfall may reflect the indirect impact of excessive snow harming tree growth [58]. Additionally, snowfall is associated with a delayed onset of the growing season and reduced radial growth [59].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, once the ecosystem warms up in spring, snowmelt water can infiltrate into soils, directly increasing plant growth by improving water availability and indirectly by enhancing microbial activity [78,81]. Secondly, extended snow cover can protect soils from extremely low temperatures and strong winds [82][83][84]. In our study area, the average temperature in winter (late October to March of the following year) is approximately −14 • C. Therefore, the thermal insulation function of snow is important, particularly early in the growing season.…”
Section: Snow Cover Duration Legacy On Vegetation Growthmentioning
confidence: 99%